Placenta-derived mesenchymal-like cells (PDA-001) as therapy for chronic pulmonary sarcoidosis: a phase 1 study - Baughman, Robert P.; Culver, Daniel A.; Jankovi, Vladimir; Fischkoff, Steven; Brockway, Giorgia; Lower, Elyse E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Placental derived mesenchymal-like cells have been found to have immunosuppressive effects on T cell function. We studied mesenchymal-like cells as immunomodulators in chronic pulmonary sarcoidosis. Methods: PDA-001 cells were culture-expanded in vitro as a plastic-adherent, undifferentiated cell population that expresses the nominal phenotype CD34-, CD10+, CD105+ and CD200+.  Four patients with refractory pulmonary sarcoidosis received two infusions of 150 million PDA-001 cells in 240 ml dextran-40 solution one week apart. During and for two hours after the first infusion, the pulmonary artery pressure was monitored. Prior to first infusion and within 24 hours after the second infusion, bronchoscopy and bronchoalveolar lavage (BAL) were performed. Patients underwent initial and serial pulmonary function testing and were followed for two years. Results: After the first infusion, all patients had a mild, non-clinically significant increase in mean pulmonary artery pressure, but none exhibited right heart failure or volume overload. In the year following treatment, there was no significant change in the FVC, but two patients had improvement in their chest x-ray and had prednisone withdrawn. BAL samples after the second infusion were sufficiently viable to undergo FACS analysis in three cases and in two patients, CD10+CD49c+C105+ cells (indicative of PDA-001 cells) were found. Conclusion: The use of placental derived mesenchymal-like cells led to a mild increase in pulmonary artery pressure. In some cases, these cells were found in the BAL 24 hours after the second dose. Two of four patients demonstrated some steroid sparing benefit, including one patient with prolonged remission. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 106-114)